Peningkatan Ekonomi Melalui Olahan Nenas Disipahutar (Amsal 10:4) - Clawdya Tampubolon; Ibelala Gea (International Forum of Researchers and Lecturers, 2024)
This article aims to improve the economy of Sipahutar residents by increasing pineapple processing. Pineapple processing can create processed pineapple products such as sweets, jams, dodol, chips, drinks, and health medicines. This research uses a qualitative method with a descriptive approach in which this method views that the data collected is the key to what is being studied. The results of this article are expected to have a positive impact on the economy of Sipahutar residents and urge residents to take a closer look at pineapple processing as a source of income energy. By referring to Proverbs 10:4 which reads,